Food protein-induced enterocolitis syndrome: a rare etiology - Janeiro, Maria Carlos (2017)
Introduction: Food protein-induced enterocolitis syndrome (FPIES) is a non-immunoglobulin E mediated gastrointestinal food hypersensitivity, probably mediated by cells. The pathophysiological mechanism remains unclear. Cow’s milk and cereals are among the most common causes of FPIES. The diagnosis is based on clinical history. Case description: We report a rare case of enterocolitis with potato in an infant with irrelevant family and neonatal history. The patient refused several times to eat the first soup (carrot and potato) and when he ingested it he had profuse vomiting with dehydration, but without the need for hospitalization. The skin prick tests with potato extract were negative and the oral food challenge was positive. Comments: The recognition of the clinical manifestations of FPIES and the awareness of the possible involvement of less common food proteins are crucial for the early diagnosis, avoiding inadequate diagnostic and therapeutic procedures.